North Atlantic Islands and a complicated wedding in Egils saga - Barreiro, Santiago Francisco
This article discusses the role of the Northern Islands in an episode of Egils saga, a medieval Icelandic text written during the first half of the thirteenth century. The episode focuses on the complexities of a wedding in which the involved groups do not have an initial agreement, developing into a conflictive situation spanning into several lands and agents. The resolution of said conflict, which involves some of the major characters in the saga, leads to a discussion of the concept of “liminality”. Its possibilities and limits for the analysis of Norse societies are here assessed through this case study. O artigo investiga o papel das ilhas do Atlântico Norte num episódio da Saga de Egill, texto medieval islandês composto na primeira metade do século XIII. Este episódio centra-se nas complexidades de um casamento, em que as diferentes partes não partem de um acordo inicial, envolvendo portanto diferentes atores e territórios habitualmente ausentes na aliança conjugal. A resolução do conflito, protagonizada por dois personagens centrais da saga, leva-nos a refletir sobre a categoria de “liminaridade”, avaliando as suas potencialidades e limitações para compreender as sociedades medievais do norte a partir deste estudo de caso. Fil: Barreiro, Santiago Francisco. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Pont. Universidad Catolica Arg."sta.maria de Los Bs.as.". Facultad de Cs. Sociales, Politicas y de la Comunicación. Instituto de Investigaciones; Argentina